The importance of concept in the landscape design process in Malaysia. - Kavousi, Shabnam; Maulan, Suhardi; Krauss, Steven Eric; Baharuddin, Mohd Nasir (2010)
Proper designs usually come from a sound concept, though some of Malaysian landscape design projects are carried out by disregarding its conceptual development. Therefore, concepts are not well defined and well-tied to their site context which results in the final design products are rendered useless and misused. Although there are several models by Motloch (2001), Milburn and Brown (2003), and Faizi and Khakzand (2007) which show the process of design, there isn’t any practical study that determines the way of considering this process in Malaysian landscape designers. The sample size for this study consists of eight professionals with more than 10 years of working experience. The researcher used in-depth interviews and focus groups to collect data from selected respondents who were chosen from Malaysian professional landscape designers through purposeful sampling. The participants were asked to draw a diagram, which is the preferable way for designers to present their thoughts. The Malaysian landscape designers’ understanding about the concept and its interaction with the influential factors such as social-cultural aspect, aesthetic, art and material in the landscape design process are investigated, through analyzing the sketches which are drawn by the respondents. In addition, the probable limitations which designer has to deal with are recognized through comparing the Malaysian landscape designers’ sketches with previous presented models. This study explores landscape designers understanding of importance and position of design concept in the landscape design process through analyzing its different steps. The output of the study aims to theoretically and practically enhance the position and importance of the design concept in the landscape design process. Correspondingly, more admirable, successful, and meaningful landscape designs will be resulted through considering the provided concept development model for being applied in landscape design process.